Preliminary Checklist of the Inshore Fishes (Chondrichthyes and Osteichthyes) of Pukan Beach, Bangka Island, Sumatra - Arifah, Nur; Effendi, Zahrial; Pragustiandi, Guntur; Hidayati, Nur Annis; Iqbal, Muhammad (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2025)
Pukan Beach is gently sloping intertidal sandy shores that have a great potential for tourist and having great number of inshore biodiversity in Bangka Island, Sumatra. A survey to collect information on species diversity of fishes has been conducted on 7 December 2024. The fishes were collected using a hand pulling fishing net as long as 5x7 m, at evening, time ranges between 4.00 p.m to 8.00 p.m. A total of 19 species of fishes from 14 families has been documented from the study site. This checklist is preliminary checklist of the species of fishes in Pukan Beach. Keywords: Bangka, coastal, hand pulling fishing net, Karimata Strait, Pes-caprae.